Editorial: Evidences (states and experiences) of land management and food/nutrition (in)security in mixed farming systems: a global perspective - Kassawmar, Tibebu; Desta, Gizaw; Tadesse, Matebu; Teferi, Ermias; Kaba, Mirgissa; Suryabhagavan, K. Venkata; Shiferaw, Abebe (2025)
The world is not on track to meet sustainable development goals for ending hunger, food insecurity, and malnutrition by 2030, with billions still lacking access to nutritious, safe, and sufficient food (Assefa et al., 2017; Iversen et al., 2023). The need to increase agricultural productivity in response to growing population has become a global concern (Wirsenius et al., 2010). As the world faces rapid population growth, climate change, and evolving market dynamics, rainfed farming systems are under increasing pressure to meet the growing demand for food and nutrition while also addressing the urgent need for environmental sustainability (Tully and Ryals, 2017). The challenge is not only to expand cultivated land and enhance agricultural productivity but also to manage land resources in ways that promote long-term ecological health, food security, and resilience to external shocks (Wani et al., 2009). One major sustainability issue is the limited agricultural space, which has become a critical concern as it is increasingly difficult to accommodate the growing of rainfed dependent rural population (Midmore, 2010). Expanding the arable landscape has been a vital strategy, but studies show that horizontal land expansion alone will not sustainably guarantee food security (Pretty, 1999). Ontop of limited agricultural space, mismanagement and progressive degradation of cultivated landscapes have worsened food insecurity, especially for smallholder farmers in developing countries (Zerssa et al., 2021). While conventional ways of enhancing grain productivity requires context-specific, innovative land use and management systems, yet effective solutions remain unclear (Wani et al., 2009). Recent recommendations underline that financing for food security and nutrition, along with effective tracking and innovative financing methods, is crucial for increasing investments needed to eradicate hunger and malnutrition (Iversen et al., 2023; Raj et al., 2022). The objective of the Research Topic were; (1) to explore innovative land use and management solutions to improve rural livelihoods and boost grain production, (2) to document the failures and success stories of land management strategies practiced across diverse regions of the world and finally (3) by highlighting the prevailing challenges in applying effective land use and livelihood systems, like the scalability issue, and indicating the need to co-designing of context and tailored land management solutions and (4) to identify and asses opportunities and challenges of addressing food security issues.